Recent Advances in Wound Healing - Aghaei, Shahin (IntechOpen, 2022)
The human wound-healing process could be divided into four discrete phases, which have also been indicated as the hemostasis, the inflammatory, the proliferation, and the remodeling phase. For a wound to be healed efficaciously, all four phases must sequentially happen at an expected time setting. Numerous aspects can hinder one or more stages of this procedure, thus can cause inappropriate or diminished wound healing. This book reviews the recent literature on the most significant factors that affect wound healing and the potential cellular and/or molecular mechanisms involved. The factors discussed include physiology of wound healing, interferon, stem cells and photobiomodulation, chronic venous ulcer, chronic fistula, bionanomaterials, topical antiseptic agents, including silver and sodium hypochlorite solution, diabetic ulcers, and nutritional supplements such as copper.